Avaliação do emprego da radiação ultravioleta na desinfecção de águas com cor e turbidez moderada - Alex Moura de Souza Aguiar (2000)
This study evaluates the application of a disinfection system using ultraviolet radiation UV in water with moderate presence of color and turbidity. An annular reactor developed at the Sanitary and Environmental Engineer Department DESA / UFMG with a 15 W UV lamp were used. Batch experiments were done using two types of synthetic water: Type 1, turbidity up to 5 TU, apparent color until 30 HU, and Type 2, turbidity between 20 and 30 TU and true color until 30 HU. The experimental waters were contaminated with Escherichia coli from strain isolated of water, in a 102 to 107 per 100 mL concentration, and submitted to UV exposition within the reactor for contact times of 1, 3 and 5 minutes. For each test the concentration of raw as well as treated samples were determined with the methodology of defined substrate. The experiments demonstrated that the complete inactivation was reached to contact times of 3 and 5 minutes. In tests with contact time of 1 minute the complete inactivation was not reached but the operational conditions were enough to reduce until 6 log of affluent cargo, with average mean between 3 and 4 log. Complementarily kinetic studies were conduced using natural surface water collected in the entrance of the Morro Redondo plant, COPASA MG. The objective of these tests was to determine the constant of inactivation of Escherichia coli and totalcoliforms to UV irradiation. The results were in accordance with the ones shown in literature. The UV dosage determination was conduced by the UFMG/PROSAB chemistry staff using the potassium ferrioxalate actinometer process. This studies allowed the admittance of the good goals of application of UV disinfection instead chlorine systems specially to small communities water supply systems.